Development and Evaluation of the Transdermal Drug-delivery System of Isradipine using Various Natural Polymers (Asian Journal of Pharmaceutics (AJP), 2022)
Introduction: Transdermal applications, relative to other routes, are non-invasive, requiring the simple adhesion ofa “patch” resulting in better patient compliance, improved bioavailability of a drug, and easy treatment termination.Hence, this investigation was aimed at delivering isradipine across intact skin as a membrane-moderated transdermaltherapeutic system of Eudragit RL100, Eudragit RS100, and Eudragit E100. Materials and Methods: An UVspectrophotometric analytical method was developed for isradipine using a double UV spectrophotometer. Themethod was validated for linearity, accuracy, and precision. Isradipine was determined in triplicate by standardtechniques. In vitro release studies in triplicate was conducted in Keshary-Chien diffusion cells across depilated rat’sabdominal skin. Hypersensitivity reaction testing on depilated rabbit’s skin was conducted. Stability of the drugs wasstudied under accelerated conditions recommended by ICH (40°C/75% R.H) for 90 days. Drug content was obtainedperiodically and compared. Log Kp of isradipine was found to be –5.337. Flux obtained from basic in vitro release(1 mg/ml) studies of isradipine was found to be 0.081 mg/cm2/h (r = 0.985). Results: The flux from isradipine fromreservoir gels IX and IA was found to be 0.034 mg/cm2/h (r = 0.985) and 0.033 mg/cm2/h (r = 0.987), respectively.The flux of membrane-moderated systems of isradipine IXRL, IARL, IXRS, IARS, IXE, and IAE was found to be0.022 mg/cm2/h (r = 0.977), 0.021 mg/cm2/h (r = 0.979), 0.020 mg/cm2/h (r = 0.977), 0.020 mg/cm2/h (r = 0.978),0.019 mg/cm2/h (r = 0.975), and 0.016 mg/cm2/h (r = 0.970), respectively. Isradipine permeates greater from xanthangum (IX) gel compared to almond gum gel and lowest flux of the series was found to be from almond gum. Kp alsotends to decrease. It was understood from the investigation that IX and almond gum can be used as drug reservoirsand Eudragit RL100, Eudragit RS100, and Eudragit E100 can be exploited as rate controlling polymeric membrane.Conclusion: The formulations released the drug in adequate amount and it is also contemplated in this study thateven when used on human skin therapeutic concentration could be achieved in the treatment of hypertension.